Safety and efficacy of loteprednol etabonate in treatment of ocular inflammatory diseases - Łazicka-Gałecka, Monika; Gałecki, Tomasz; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Topical corticosteroid drops are routinely used after cataract surgery, glaucoma surgery, keratoplasty and in treatment of ocular inflammatory diseases. By inhibiting the activation of phospholipase A2, corticosteroids prevent arachidonic acid formation like prostaglandins, prostacyclin and leukotrienes. Compared with dexamethasone, their binding affinity to a glucocorticoid receptor was 4.3 times higher. Long term use of topical steroids is likely to induce adverse effects, such as elevated intraocular pressure, which can lead to glaucoma. Loteprednol etabonate is rapidly metabolized by tissue esterases, limiting its concentration in ciliary body and thus reducing the risk of adverse effects. Due to its chemical structure, loteprednol etabonate does not form covalent bonds with crystalline lens proteins, which prevents cataract formation. Loteprednol etabonate is a very potent anti-inflammatory agent and its administration is associated with a decreased risk of side effects.